Penanganan Terkini Metastasis Kelenjar Getah Bening pada Karsinoma Sel Skuamus (KSS) Penis - RAKHMAN, MOCHAMMAD REZA ARIEF; UMBAS, RAINY (Indonesian Journal of Cancer, 2014)
Recently, the incidence of penile cancer were increased. Two tertier hospital in Jakarta reporting an escalation in the average penile cancer patients from 1,8 to 6,2 per year in the last 16 years (1988-2005). The incidence of regional lymph node metastases was affected by the tumour grading. Only 2 out of 47 cases (4%) in Tis or Ta, 5 out of 73 cases in pT1 (G1/G1-2) and 9 out of 24 cases (38%) in pT1 (G2). 59% inguinal metastase was discovered in pT2. 5 years survival rate was 95% in negative lymphatic nodes, 76% in positive lymphatic node and 0% when pelvic metastatic was found.This study provides information about recent treatments for lymph node metastase in penile squamus cell carcinoma (SCC). Treatment for regional lymph node metastase by NCCN guidelines depends on tumour grade, palpability, nodul size, mobility, unilateral or bilateral. The treatment itself can be surgical (ILND,PLND), radiotherapy and chemotherapy